Analisis Kerusakan Jalan Menggunakan Metode Pavement Condition Index (PCI) dan Surface Distress Index (SDI) Jalan Imam Bonjol-Tangerang - Rizki Hidayatullah (Jurnal Proyek Teknik Sipil, 2026)
Roads are one of the most important land transportation infrastructures that social and economic activities. Road damage reduces the level of service, increases transportation costs, and poses accident risks. This study aims to analyze the road condition, traffic volume, and maintenance strategy on Imam Bonjol Street, Tangerang, using the Pavement Condition Index (PCI), Surface Distress Index (SDI), and PKJI 2023 guidelines. The results show that the average PCI value is 58,07 (Poor category), with 75% of road segments in Poor condition, 20% Fair, and 5% Very Poor. The SDI values range from 0-55, indicating good to moderate condition. Traffic volume analysis reveals the dominance of passenger cars and motorcycles with peak flows in the morning and evening. Recommended maintenance strategies include structural rehabilitation for severely damaged segments, overlay for moderate damage, and routine maintenance for still-serviceable sections. These findings are expected to provide a basis for prioritizing road maintenance effectively and efficiently.